2010
DOI: 10.1007/s10059-010-0112-1
|View full text |Cite
|
Sign up to set email alerts
|

A DnaJ-like Homolog from Cryphonectria parasitica Is Not Responsive to Hypoviral Infection but Is Important for Fungal Growth in Both Wild-Type and Hypovirulent Strains

Abstract: A DnaJ-like gene, Cpdj1, a molecular chaperone and regulator of Hsp70 in Cryphonectria parasitica, was characterized. The protein product of Cpdj1 gene consists of 379 amino acids with a predicted molecular mass of 40.6 kDa and a pI of 7.79. The deduced protein sequence revealed preservation of the conserved hall-mark J-region and exhibited high homolo y to all known DnaJ-like proteins. Disruption of the Cpdj1 gene resulted in slow growth and produced colonies characterized by retarded growth and deep orange c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previously, heat shock proteins such as Hsp70 and Hsp90 were shown to be required for the virulence of fungal pathogens and have been proposed as potential antifungal therapeutic targets (Cowen et al, 2009;Brown et al, 2010;Sun et al, 2010;Nagao et al, 2012;Cowen, 2013;Cordeiro et al, 2016;Tiwari and Shankar, 2018;Weissman et al, 2020). Along with these major classes of chaperones, the co-chaperones also play important roles in virulence and the elaboration of virulence-related traits such as dimorphic switching, effector secretion, and polysaccharide capsule formation (Lim et al, 2010;Lo Presti et al, 2016;Xie et al, 2017;Horianopoulos et al, 2020;Jurick et al, 2020;Son et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, heat shock proteins such as Hsp70 and Hsp90 were shown to be required for the virulence of fungal pathogens and have been proposed as potential antifungal therapeutic targets (Cowen et al, 2009;Brown et al, 2010;Sun et al, 2010;Nagao et al, 2012;Cowen, 2013;Cordeiro et al, 2016;Tiwari and Shankar, 2018;Weissman et al, 2020). Along with these major classes of chaperones, the co-chaperones also play important roles in virulence and the elaboration of virulence-related traits such as dimorphic switching, effector secretion, and polysaccharide capsule formation (Lim et al, 2010;Lo Presti et al, 2016;Xie et al, 2017;Horianopoulos et al, 2020;Jurick et al, 2020;Son et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic analysis of transcripts and proteins of both virus‐free and virus‐infected isogenic strains of C. parasitica has revealed that these phenotypic changes are attributable to hypoviral modulations in the fungal gene expression profiles (Allen & Nuss, 2004 ; Allen et al, 2003 ; Chun et al, 2020 ; Deng et al, 2007 ; Kang et al, 1999 ; Kazmierczak et al, 1996 , 2012 ; Kim et al, 2012 ; Wang et al, 2013 ). Among the several fungal pathways regulated by the hypovirus infection, the stress‐response pathway, which includes specific heat‐shock proteins, has been shown to be one of the specific targets perturbed by the hypovirus infection (Allen & Nuss, 2004 ; Allen et al, 2003 ; Baek et al, 2014 ; Lim et al, 2010 ). Our previous studies using a growth condition supplemented with tannic acid (TA), which is abundant in the bark of chestnut trees and is assumed to be the major defence material against pathogen infection, demonstrated that a gene encoding a co‐chaperone of heat‐shock protein 90 is specifically regulated by the presence of hypovirus CHV1 and TA supplementation (Kim et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%